Hastings Alumni Association-Fresno Chapter Luncheon Honoring Justice Donald Franson, Sr. - Watkins, Howard::::::::: (1988)
Steve Franson, Kathy Franson, Donald Franson, Irma Franson, and Tom Franson Luncheon held at the Downtown Club